THE IMPLICATION OF SOCIAL POLICIES IN ENHANCING EQUALITY IN PERI-URBAN LAND MARKET IN BAGAMOYO DISTRICT, TANZANIA - Nelly John Babere (African Journal on Land Policy and Geospatial Sciences, 2018)
Population increase influence the dynamics in land market and agitate land access competition, which results into exclusion of some individuals. Inequality is evident in majority of Tanzanians women, youth, children and elderly. It is more prevalence in land markets where rich individuals are favorable to make choices regarding access to land resources. Owing to potential developments, peri-urban areas are becoming places where changes in land uses and activities take place. This study analyzed how gender policy facilitated access to land market by the disadvantaged poor in Bagamoyo District. It was evident that disadvantaged poor was the most affected group in accessing land markets. Nevertheless, enforcement of Gender policy has a positive influence to the disadvantaged poor. For stance it has facilitated, the district to contribute 20% off its budget towards disadvantaged groups’ investment capital. Therefore, more emphasis on gender policy implementation is needed to enhance equal access to land markets.